ANALISIS QUALITY OF SERVICE APLIKASI VOICE OVER INTERNET PROTOCAL PADA JARINGAN MOBILE ADHOC NETWORK (Protocol Voice Over Application Quality Of Service Analysis On Adhoc Network Mobile Network) - Riklan Kango; Irawan Ibrahim (Jurnal Sains Informasi Geografi, 2018)
Abstract – The The development trend of computer networks is currently more likely to Wireless networks because the practicality of Wireless networks and their performance is almost the same as wired networks, one of the applications of Wireless networks is the exchange of voice information by using Voice over Internet Protocol (VoIP) technology. The long-term goal of this research is as part of the realization of next-generation network communication in Indonesia based on IP which has the urgency of developing communication media between the sender and receiver of voice information by minimizing the cable network component, namely replacing it with Mobile Adhoc Network (MANET). namely the ad-hoc communication model based on wireless networks. The type of research used is experimental research, namely laboratory-based research using the Network Development Life Cycle method. The Quality of Service factors tested were delay, jitter, throughput and packet loss. This research implements VoIP technology using the MANET network where transmission media is Wireless so that duration is an influential thing. Therefore, the duration of the experiment in this study was 180 seconds. Retrieval of test data using Wireshark Software. The results showed that VoIP communication using the MANET network with a defined duration standard resulted in a relatively good performance for all tests meeting the established standards so that it was feasible to be implemented on the MANET network. The overall test results using the data flow and testing without the data flow obtained results that are relatively the same so it can be concluded that the VoIP network that has been built is quite satisfactory. Keywords: Ad-hoc, Manet, Voip, Qos Abstrak – Trend perkembangan jaringan komputer saat ini lebih cenderung kepada jaringan Wireless karena kepraktisannya jaringan Wireless dan performansinya hampir sama dengan jaringan kabel, salah satu pengaplikasian jaringan Wireless adalah pertukaran informasi suara dengan menggunakan teknologi Voice over Internet Protocol (VoIP). Tujuan jangka panjang penelitian ini adalah sebagai bagian dari realisasi komunikasi jaringan masa depan (next generation network) di Indonesia yang berbasiskan IP yang memiliki urgensi pengembangan media komunikasi antara pengirim dan penerima informasi suara dengan meminimalis komponen jaringan kabel yaitu menggantinya dengan jaringan Mobile Adhoc Network (MANET) yakni model komunikasi ad-hoc berbasiskan wireless network. Jenis penelitian yang digunakan adalah penelitian experimental yaitu penelitian laboratory-based-research dengan menggunakan metode Network Devolopment Life Cycle. Adapun faktor-faktor Quality of Service yang diuji adalah delay, jitter, throughput dan packet loss. Penelitian ini, megimplementasikan Teknologi VoIP dengan menggunakan jaringan MANET dimana media transmisi adalah wireless sehingga durasi adalah hal yang berpengaruh. Oleh sebab itu, durasi percobaan dalam penelitian ini 180 second. Pengambilan data pengujian menggunakan Software Wireshark. Hasil penelitian menunjukkan komunikasi VoIP menggunakan jaringan MANET dengan standar durasi yang ditetapkan menghasilkan performansi yang tergolong baik untuk seluruh pengujian memenuhi standar yang ditetapkan sehingga layak untuk diimplementasikan pada jaringan MANET. Hasil pengujian secara keseluruhan pengujian menggunakan aliran data dan pengujian tanpa aliran data didapatkan hasil yang relatif sama dengan demikian dapat disimpulkan jaringan VoIP yang telah dibangun cukup memuaskan. Kata kunci: Ad-hoc, Manet, Voip, Qos